Relationship Of Predisposition Factors Using Of VCT By Mother With HIV / AIDS In Yogyakarta - Sundari Mulyaningsih; Arantika Meidya Pratiwi (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2019)
The HIV / AIDS cases in Indonesia is increasing and the spread is very complex. This research is a quantitative study with analytical survey research methods. The population was 37 HIV / AIDS mothers taken by total population at IPPI Foundation Yogyakarta. Data were analyzed by Chi-Square and it was found that most respondents had good knowledge about HIV / AIDS (94.6%), and were well-informed about the use of VCT (81.1%). The results of the correlation (p value: 0.532) did not have the demographic significance of respondents with the use of VCT services, (p value: 0.065) had no significance of knowledge of HIV / AIDS with the use of VCT services, (p value: 0.048) utilization of VCT services. The results of the study can concluded that there is no association of predisposing factors with the use of VCT services. There is a relationship between knowledge about VCT services and utilization of VCT services. Based on the results, needed to maintain and further improve VCT services in improving the health status of mothers with HIV / AIDS